Analysis of cases of moose (Alces alces) occurrence in the transformed environment of Kyiv - E. I. Ivanenko (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Екологія)
Purpose. Justification and application of the analysis method of moose occurrence in Kyiv based on mass media data with further analysis of its spatial and chronological distribution.